Innovation In Sharia Financial Products To Drive Sustainable Economic Growth - Muhammad Khoirun Nasirin; Ahmad Zainul Abidin; Rakhmawan Habibi; Ahmad Syahni (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2026)
This study aims to analyze innovations in Islamic financial products in driving sustainable economic growth. The study employed a descriptive qualitative method with a literature review approach through analysis of various journals, regulations, and scientific reports. The study results indicate that product innovations such as green sukuk , Islamic fintech, productive waqf, Islamic mutual funds, and inclusive financing contribute to increasing financial inclusion and literacy, expanding access to financing for MSMEs, and supporting the achievement of the Sustainable Development Goals (SDGs). However, the development of Islamic finance still faces challenges such as low public literacy, limited regulations, the quality of human resources, and digital infrastructure. Therefore, regulatory strengthening, inter-institutional collaboration, increased literacy, and accelerated digital transformation are needed so that Islamic financial innovation can strengthen inclusive and sustainable economic development